Beautiful Trouble or How To Move Between Art and Revolt - Ramírez, Julia (Re-visiones, 2024)
Beautiful Trouble. A Toolbox for Revolution. Andrew Boyd and Dave Oswald Mitchell (eds.). OR Books, New York and London 2012, 450 pages